Technological Innovation in Clean Water Management to Improve the Quality of Life of the Community - Ridha, Muhammad Abdi; Hutagalung, Carli Apriansyah (MSJ : Majority Science Journal, 2025)
Clean water is a basic need that is very important for human health, well-being, and quality of life. However, many regions in the world, including Indonesia, still face serious challenges in providing clean water due to population growth, urbanization, environmental pollution, climate change, and inadequate infrastructure. This article aims to examine various technological innovations in clean water management and analyze their impact on people's quality of life. This study uses the Systematic Literature Review (SLR) method by examining various scientific articles, policy reports, and relevant technical documents from various reliable sources. The results of the study show that the application of technologies such as membrane filtration, Internet of Things (IoT)-based water quality monitoring, integrated wastewater treatment, desalination technology, and the use of renewable energy significantly increase access to clean water, reduce the rate of disease, and support economic welfare and environmental resilience of the community. This article recommends the integration of inclusive and collaborative clean water technology policies to realize efficient, sustainable, and equitable water management at all levels of society